1979
DOI: 10.1038/bjc.1979.29
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial cancer in Hong Kong 1976-1977

Abstract: Summary.-Bronchial cancer is a disease of high and increasing annual incidence in Hong Kong, especially in women, whose age-specific death rates from this cause are amongst the highest in the world.A case-control study of the relationship of bronchial cancer with smoking was carried out during 1976-77, taking particular note of the histological type of the tumour. Two hundred and eight male and 189 female patients were interviewed, covering about half the total number of cases of bronchial cancer registered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…The predicted effect of cigarette consumption on lung-cancer incidence was improved by restriction to only epidermoid and smallcell types (Table V) again as might be expected (Kreyberg, 1962). The decrease in the regression coefficient with lung cancer when sex was controlled in the multiple regression analysis may be due in part to the relatively high lung-cancer rates which we and others have observed among Chinese women in spite of their low rate of smoking (MacLennan et al, 1977;Chan et al, 1979).…”
Section: Discussionmentioning
confidence: 65%
“…The predicted effect of cigarette consumption on lung-cancer incidence was improved by restriction to only epidermoid and smallcell types (Table V) again as might be expected (Kreyberg, 1962). The decrease in the regression coefficient with lung cancer when sex was controlled in the multiple regression analysis may be due in part to the relatively high lung-cancer rates which we and others have observed among Chinese women in spite of their low rate of smoking (MacLennan et al, 1977;Chan et al, 1979).…”
Section: Discussionmentioning
confidence: 65%
“…In an earlier series by Chan et al (1979) Lee & T'so (1963) and in more detail with those of Chan & MacLennan (1977).…”
Section: Discussion Resultsmentioning
confidence: 91%
“…Although the concept that adenocarcinoma is not related to smoking has been popular since Doll et al (1957) and Kreyberg (1962) published their reports, this view has been disputed by other investigators (Kennedy, 1973;Belcher, 1975 (Chan et al, 1979;MacLennan et al, 1977). In fact, 61% of the females with adenocarcinoma did not smoke (Lam et al, 1983).…”
Section: Discussion Resultsmentioning
confidence: 99%
“…The present study was a case control study on lung cancer in Hong Kong Chinese women with a larger number of subjects included than in the two previous local case control studies (Chan et al, 1979;Koo et al, 1984). All our cases were pathologically confirmed, unlike these two previous studies which included cases confirmed only by clinicoradiological criteria.…”
Section: Discussionmentioning
confidence: 97%
“…The most common cell type in males is squamous cell carcinoma (33.3%) and in females, adenocarcinoma (49.6%) (Kung et al, 1984). A case control study in 1976-1977 confirmed the relationship between lung cancer and smoking in males, but in females about half the lung cancer patients were found to be non-smokers, of whom two thirds were suffering from adenocarcinoma (Chan et al, 1979). Further studies on passive smoking and other risk factors have been carried out in Hong Kong but they failed to throw much light on the causes of lung cancer in never smoking females (Chan & Fung, 1982;Lam et al, 1983;Koo et al, 1984;Koo et al, 1985).…”
mentioning
confidence: 92%